EDUCATION ROLES OF NURSES IN CLINICAL SETTING - Batiha, Mustafa Abdelrhman (European Scientific Journal, ESJ, 2015)
Nurses have crucial roles in clinical settings since they are the first line in treating patients and they are also forming the last line in contact with patients. Furthermore, clinical settings include a variety of clinical staff including physicians, residents, nurses, and students. Nurses have also significant teaching roles for students and new involved nurses in career. In this study, we put emphasis in living experience of nurses as educators. The literature was reviewed to retrieve proper material in this issue.